The Role of the Mover Teacher and Non-Mover Teacher in Realizing Independent Learning in Merdeka Curriculum - Renny Nur Afida; Haryono Haryono; Titi Prihatin (Journal of Innovative Technology and Sustainability Education, 2027)
Objective: The purpose of this study is to understand teachers' perspectives as spearheads of curriculum actors at the operational level regarding the roles of movers and non-movers in realizing independent learning in the Merdeka Curriculum. Method: Through a qualitative approach with a phenomenological method using Interpretative Phenomenological Analysis (IPA) with the help of the ATLAS.ti application. The research was conducted at SD Rapah 02, a non-mover school, and SD Negeri Ungaran 5, a mover school. Data collection was conducted through observation, in-depth interviews, and documentation studies using method and source triangulation and data validation. Results: The main role of mover teachers and non-mover teachers is to support independent learning in students. They both act as facilitators and motivators, encourage students to learn actively and creatively, motivate students to want to learn by creating interactive, innovative, and interesting learning experiences so that students are not easily bored, and build a conducive classroom environment. Meanwhile, the difference is that the Mover Teacher has an additional role as an agent of educational transformation, one who reflects, shares, and collaborates. Novelty: This study provides new empirical evidence that the Mover Teacher Program's added value extends beyond improving classroom practices. The program strengthens teachers' capacity to lead educational transformation through collaboration, reflective practice, and knowledge dissemination, suggesting that its impact reaches school-wide professional development.